2003
DOI: 10.1093/emboj/cdg537
|View full text |Cite|
|
Sign up to set email alerts
|

Caspase-12 and endoplasmic reticulum stress mediate neurotoxicity of pathological prion protein

Abstract: Prion diseases are characterized by accumulation of misfolded prion protein (PrP Sc ), and neuronal death by apoptosis. Here we show that nanomolar concentrations of puri®ed PrP Sc from mouse scrapie brain induce apoptosis of N2A neuroblastoma cells. PrP Sc toxicity was associated with an increase of intracellular calcium released from endoplasmic reticulum (ER) and up-regulation of several ER chaperones. Caspase-12 activation was detected in cells treated with PrP Sc , and cellular death was inhibited by over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
341
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(364 citation statements)
references
References 38 publications
18
341
0
5
Order By: Relevance
“…55 In keeping with this, brain tissue from PrP Sc -infected mice and patients with Creutzfeldt-Jakob disease showed higher levels of caspase-12. 55 This data indicates that the activation of ER stress and caspase-12 may play a role in neuronal apoptosis associated with the accumulation of mutant prion protein in neurons. It was reported that in the murine scrapie model, the accumulation of PrP Sc was closely followed by the induction of the ER chaperone Grp58.…”
Section: Er Stress and Transmissible Spongiform Encephalopathymentioning
confidence: 58%
See 2 more Smart Citations
“…55 In keeping with this, brain tissue from PrP Sc -infected mice and patients with Creutzfeldt-Jakob disease showed higher levels of caspase-12. 55 This data indicates that the activation of ER stress and caspase-12 may play a role in neuronal apoptosis associated with the accumulation of mutant prion protein in neurons. It was reported that in the murine scrapie model, the accumulation of PrP Sc was closely followed by the induction of the ER chaperone Grp58.…”
Section: Er Stress and Transmissible Spongiform Encephalopathymentioning
confidence: 58%
“…N2A neuroblastoma cells treated with PrP Sc produce a fast and sustained increase in intracellular calcium levels. 55 Pretreatment with thapsigargin that depletes ER calcium stores reduced the increase in calcium observed with PrP Sc . 55 This indicates that the ER is involved in the mechanisms by which PrP Sc acts in nerve cells.…”
Section: Er Stress and Transmissible Spongiform Encephalopathymentioning
confidence: 99%
See 1 more Smart Citation
“…39 In addition, caspase-12 was shown to participate in the development of ER-stress-related neurodegenerative disorders such as Alzheimer's disease or prion associated diseases. 39,40 Whereas degradation or proteolysis of caspase-12 is a well-established hallmark of ER stress, its central role in ER-stress-induced apoptosis was challenged by various studies. [41][42][43] The precise function of caspase-12 in this particular pathway is yet unclear and controversial.…”
Section: Caspase-1 and It Substrate Il-1bmentioning
confidence: 99%
“…For instance, infection with several murine prion strains impairs the cell response of GT1 and N2a cells to oxidative stress [89], presumably through a decrease in superoxide dismutase activity. RML infection was also shown to sensitise N2a and GT1 cells to pro-apoptotic stimuli such as endoplasmic reticulum stress or to mild proteasome inhibition [54,71]. However, it is important to point out that prion-infected cell lines accumulating infectious titres similar to those in brain tissue do not show any obvious cytopathic effect, with the possible exception of RML-infected GT1 cells that inconsistently undergo apoptosis.…”
Section: Mechanisms Of Neurodegenerationmentioning
confidence: 99%